2016
DOI: 10.1007/s00038-016-0927-4
|View full text |Cite
|
Sign up to set email alerts
|

Is personality a driving force for socioeconomic differences in young adults’ health care use? A prospective cohort study

Abstract: ObjectivesTo relate personality characteristics at the age of 12 to socioeconomic differences in health care use in young adulthood. And thereby examining the extent to which socioeconomic differences in the use of health care in young adulthood are based on differences in personality characteristics, independent of the (parental) socioeconomic background.MethodsPersonality of more than 13,000 Dutch 12-year old participants was related to their health and socioeconomic position after a follow-up of 13 years (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…This might be explained by a lack of statistical power. Moreover, a recent study showed that only high neuroticism was associated with HCU among Dutch young adults [ 66 ], whereas the other personality factors were not associated with high GP costs (dichotomized outcome measure with low and high GP costs). However, we expect that significant associations between personality factors and HCU (particularly with mental HCU [ 67 ]) might appear in a large sample representing the general population [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by a lack of statistical power. Moreover, a recent study showed that only high neuroticism was associated with HCU among Dutch young adults [ 66 ], whereas the other personality factors were not associated with high GP costs (dichotomized outcome measure with low and high GP costs). However, we expect that significant associations between personality factors and HCU (particularly with mental HCU [ 67 ]) might appear in a large sample representing the general population [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the exclusion of missing cases due to death (N = 58), incomplete intelligence tests (N = 6545), and missing covariates (N = 5093), 10,400 participants (53.6%) remained for the analyses. More in-depth information can be found in Kraft, Traag, Arts, Otten, and Bosma (2016).…”
Section: Study Populationmentioning
confidence: 99%